Relationship between Grocery Shopping Frequency and Home- and Individual-level Diet Quality among Low-income Racial/Ethnic Minority Households with Preschool-age Children - Banks, Justin (J Acad Nutr Diet, 2020)
BACKGROUND: The home food environment can shape the diets of young children. However, little is known about modifiable factors that influence home food availability and dietary intake. OBJECTIVE: The purpose of this study was to examine the relationship between grocery shopping frequency with home- and individual-level diet quality. DESIGN: This was a secondary, cross-sectional analyses of data from the Study on Children’s Home Food Availability using TechNology (SCAN). Data were collected in the homes of participants from November 2014 through March 2016. PARTICIPANTS/SETTINGS: A purposive sample of ninety-seven low-income African American and Hispanic/Latinx parent-child dyads residing in Chicago, IL enrolled in the study. MAIN OUTCOME MEASURES: The main outcomes were home- and individual-level diet quality. Healthy Eating Index-2010 (HEI-2010) scores were calculated from home food inventory data collected in participants’ homes to assess home-level diet quality. To assess individual-level diet quality, HEI-2010 scores were based on multiple 24-hour diet recalls from parent-child dyads. STATISTICAL ANALYSES: Grocery shopping frequency was examined in relation to diet quality at the home and individual levels. Grocery shopping frequency was defined as the number of times households shopped on a monthly basis (i.e. once/month, twice/month, three times/month, or four times/month or more). Multivariable linear regression analysis, controlling for covariates, tested the relationships between grocery shopping frequency and HEI-2010 total and component scores at the home- and individual-levels. RESULTS: Grocery shopping frequency was positively associated with home-level HEI-2010 scores for total diet, whole grains, and empty calories (higher scores reflect better diet quality) and with individual-level HEI-2010 scores for total and whole fruit (parents only), vegetables (children only), and sodium (children only). CONCLUSIONS: Grocery shopping frequency was associated with multiple dimensions of diet quality at the home- and individual- levels. These results offer a potential strategy to intervene on home food availability and individual dietary intake.